Quantitation of CDH1 promoter methylation in formalin-fixed paraffin-embedded tissues of breast cancer patients using differential high resolution melting analysis - Naghitorabi, Mojgan (Adv Biomed Res, 2016)
BACKGROUND: E-cadherin (CDH1) plays an important role in cell–cell adhesion of epithelial tissues. Loss of E-cadherin expression can lead to loss of tissue integrity, metastasis, and cancer progression. Also loss of E-cadherin expression might be related to aberrant promoter methylation of the CDH1 gene. Many studies have been performed on CDH1 promoter methylation, especially in breast cancer. Although most of the studies have used qualitative methods for methylation analysis, this study is designed to quantitatively investigate CDH1 promoter methylation in breast cancer and its correlation with patients’ clinicopathological features. MATERIALS AND METHODS: Using differential high resolution melting analysis (D-HRMA), the methylation level of the CDH1 gene promoter was quantified in 98 breast cancer formalin-fixed paraffin-embedded (FFPE) tissues and also 10 fresh frozen normal breast tissues. RESULTS: All samples were detected to be methylated at the CDH1 promoter region. About 74.5% of the breast cancer samples were hypermethylated with an average methylation level of around 60%, while 25.5% of the patients were methylated with the mean methylation level of about 33%, and 90% of the normal samples had a mean methylation level of about 18%. Statistical analyses represented a significant correlation between CDH1 promoter methylation and cancer progression hallmarks, such as, clinical stage, nodal involvement, tumor size, and histological grade. CONCLUSION: In summary, quantitation of CDH1 promoter methylation can serve as a diagnostic and prognostic tool in breast cancer. Also D-HRMA can be used as a fast and reliable method for quantitation of promoter methylation.